Man versus the state - "Spencer, Herbert" (London, 1950)
The drift of legistation since that time has been of the kind anticipated.Dictatorial measure, rapidly multiplied, have tended continually to narrow the liberties of individuals; and have done this in a double way.
Keywords: Political science